“Pengaruh Adversity Quotient Terhadap Kinerja Karyawan Melalui Motivasi Kerja Sebagai Variabel Intervening (“Studi Pada Pengemudi Taksi Konvensional di Kota Medan)” - Anggia Sari Lubis (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2018)
Abstract            The purpose of this study is to analyze and determine the effect of adversity quotient on Employee Pe-formance Through Job Motivation as an intervening variable in the conventional taxi driver in Medan. The nature of this study was associative,and the type of this research was quantitative. A sample of this research are 253 conventional taxi driver in Medan. The data that has been collected through a valid and reliable questionnaire, then processed using Path analysis approach. Results of this study are (1) adversity quotient has positive effect and significant effect on the employee performance, (2) adversity quotient has positive and significant effect on job motivation, (3) Job motivation has a positive and significant effect on the employee performance, (4) Job motivation was not as a perfect mediation between adversity quotient and employee performance. .